Religious Education, Peacebuilding, and Democratic Citizenship in Nigeria: A Curriculum and Pedagogical Analysis - Isiaq Oluwatosin Yahya; Sanni Mufutau Olayiwola; Asade Wahab Adeshola; Kewulere Adam Olasunkanmi; Yusuf Lawal Ayantunde (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
Nigeria’s multi-religious and pluralistic society continues to experience persistent tensions and conflicts, highlighting the urgent need for educational strategies that promote democratic citizenship and sustainable peace. This study presents a conceptual and curriculum-based analysis of the role of Religious Education (RE) in advancing peacebuilding and democratic engagement in Nigeria. Drawing on existing literature and policy frameworks, the paper critiques the predominantly confessional and doctrinal orientation of current RE curricula, particularly Christian Religious Studies (CRS) and Islamic Religious Studies (IRS), which often marginalise interreligious literacy, critical civic competencies, and peace-oriented content. The analysis identifies key gaps in curriculum design, pedagogical practices, and systemic implementation, including inadequate teacher training, weak integration of peace education, and the challenges associated with merging religious and civic education into composite subjects such as “Religion and National Values.” The paper argues for comprehensive curriculum reform that incorporates pluralistic perspectives, embeds peace education across disciplines, and strengthens the nexus between religious ethics, human rights, and democratic citizenship. It further emphasises the adoption of dialogic and participatory pedagogies, alongside strengthened school–community partnerships, to enhance contextual relevance and social cohesion. The study concludes that a reconceptualised and inclusive Religious Education framework can serve as a strategic tool for nurturing ethically grounded and socially responsible citizens capable of contributing to Nigeria’s democratic consolidation and long-term peace.